(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the prevalence of Chronic Fatigue Syndrome among physicians working in anesthesiology and reanimatology and its impact on professional performance. The study analyzes occupational risk factors such as prolonged working hours, night shifts, high emotional stress, and continuous exposure to critically ill patients contributing to the development of chronic fatigue. It is demonstrated that chronic fatigue negatively affects cognitive functions, including attention, memory, and clinical decision-making, leading to decreased work efficiency and an increased risk of medical errors. The relationship between chronic fatigue and burnout syndrome is also explored, highlighting their combined negative effects on physicians’ well-being and patient safety. Organizational and individual factors contributing to fatigue are identified, and modern pedagogical approaches to its prevention and management are proposed. The findings emphasize the importance of optimizing work schedules, improving working conditions, and implementing psychological support systems.